2015
DOI: 10.1109/tip.2014.2383327
|View full text |Cite
|
Sign up to set email alerts
|

3D Visual Discomfort Predictor: Analysis of Disparity and Neural Activity Statistics

Abstract: Being able to predict the degree of visual discomfort that is felt when viewing stereoscopic 3D (S3D) images is an important goal toward ameliorating causative factors, such as excessive horizontal disparity, misalignments or mismatches between the left and right views of stereo pairs, or conflicts between different depth cues. Ideally, such a model should account for such factors as capture and viewing geometries, the distribution of disparities, and the responses of visual neurons. When viewing modern 3D dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Inaccuracies of stereo content as demonstrated in this study play a major role in 3D induced fatigue and 3D-induced discomfort. 37 It can thus be assumed that decreased realism of 3D perception in static stereo images shows the potential to increase fatigue in digital surgical systems. Artificial stereo-induced fatigue has been measured extensively.…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Inaccuracies of stereo content as demonstrated in this study play a major role in 3D induced fatigue and 3D-induced discomfort. 37 It can thus be assumed that decreased realism of 3D perception in static stereo images shows the potential to increase fatigue in digital surgical systems. Artificial stereo-induced fatigue has been measured extensively.…”
Section: Fatiguementioning
confidence: 99%
“…Artificial stereo-induced fatigue has been measured extensively. 13,17,19,22,30,31,34,[37][38][39][40][41][42] Target applications evaluated were mainly the commodity use of stereo content, in TV, cinema, or gaming VR. 20,21,[43][44][45][46] Fatigue after viewing of 3D content is a well-reproduced phenomenon; its occurrence is temporary and limited to the duration of use and some hours thereafter.…”
Section: Fatiguementioning
confidence: 99%
“…TV watching experience comprises diverse elements. In previous studies on TV watching experience, presence [1,[16][17][18][19], visual comfort [20][21][22][23][24][25][26], image quality [17,27,28], satisfaction [26], visual fatigue [26,[29][30][31], motion sickness [16], empirical 3-dimensional (3D) image distortion [21], and emotional reactions [28] were considered. User satisfaction is used to explain the overall quality of experience with visual display products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, many TV watching experience elements have been considered: presence [16,19], visual comfort [24,26], image quality [17,28], satisfaction [26], visual fatigue [26,29], motion sickness [16,57], image distortion [21], and emotional reactions [28]. The spatial presence felt by a display user can act as a predictor for user satisfaction [58].…”
Section: Introductionmentioning
confidence: 99%
“…The intelligent lighting system is not used only in the nighttime; it also can be employed as a light compensation tool to solve complex environment light source problems or uneven illumination distribution problems during the daytime. Improper lighting will decrease working efficiency [5], affect task scheduling, or even cause some accidents. For example, in our past research work it can be found that the visual fatigue and the human error rate may be increased when an astronaut participates in some aerospace flight tasks under improper environment lighting [6].…”
Section: Introductionmentioning
confidence: 99%